2022
DOI: 10.1111/vsu.13803
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and severity of short‐term incisional complications after intraoperative local infiltration of liposomal bupivacaine in dogs

Abstract: Objective To report the incidence of short‐term incisional complications in dogs receiving intraoperative local infiltration of liposomal bupivacaine. Study design Retrospective study. Animals Client‐owned dogs (n = 218). Methods Medical records were searched for dogs whose surgical site was infiltrated with liposomal bupivacaine. Records were reviewed for complications within 20 days postoperatively. Cases were categorized by: (1) surgical wound classification (clean, clean‐contaminated, contaminated); (2) la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Liposomal bupivacaine (5.3 mg/kg) was locally infiltrated by the surgeon at the end of surgery in 65 dogs but the exact tissue layer and timing varied: "before abdominal wall closure" (21 dogs), "after abdominal wall closure" (2), external rectus muscle (1), subcutaneous (11), injected within the body of the external rectus muscle and subcutaneous (10), T A B L E 1 Patient parameters and surgical information for the dogs that received LB and those that did not. Note: A Wilcoxon rank sum test was used to determine difference between groups, with median (range) stated.…”
Section: Perioperative and Lb Administration Datamentioning
confidence: 99%
See 2 more Smart Citations
“…Liposomal bupivacaine (5.3 mg/kg) was locally infiltrated by the surgeon at the end of surgery in 65 dogs but the exact tissue layer and timing varied: "before abdominal wall closure" (21 dogs), "after abdominal wall closure" (2), external rectus muscle (1), subcutaneous (11), injected within the body of the external rectus muscle and subcutaneous (10), T A B L E 1 Patient parameters and surgical information for the dogs that received LB and those that did not. Note: A Wilcoxon rank sum test was used to determine difference between groups, with median (range) stated.…”
Section: Perioperative and Lb Administration Datamentioning
confidence: 99%
“…4 More recently, local incisional complications have been reported in 43/218 canine surgeries (19.7%) with local infiltration of LB, with a higher incidence in soft tissue (32/123; 26.0%) than orthopedic (11/95; 11.6%) procedures. 11 Complications were noted more commonly in contaminated (30.8%) than in clean (18.8%), or cleancontaminated (23.1%) surgeries. In a prospective canine study, redness and inflammation around the laparotomy incisions treated with LB was observed in 276/321 dogs in hospital and in 80 at the 2 week recheck.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…8 This study did not report the bacterium isolated, nor did it indicate whether dogs diagnosed with SSI had surgeries performed under clean-contaminated or dirty conditions. Another study 9 found that the incidence of wound complications after infiltration of liposomal bupivacaine in dogs did not vary significantly between clean, clean-contaminated, and dirty surgeries but that the overall wound complication rate was 19.7%, with contaminated and clean-contaminated surgeries having high complication rates of 30.8% and 23.1%, respectively. The overall rate of SSI reported was 5%, but the rate of SSI for clean, clean-contaminated, or contaminated surgeries was not reported.…”
mentioning
confidence: 97%
“…The overall rate of SSI reported was 5%, but the rate of SSI for clean, clean-contaminated, or contaminated surgeries was not reported. 9 In human medicine, SSI is listed as a potential complication of liposomal bupivacaine administration. Some reports support an increased risk of SSI with use of liposomal bupivacaine, particularly in skin graft donor sites and after arthroplasty.…”
mentioning
confidence: 99%